Antiamyloidogenic Activity of Aβ42‐Binding Peptoid in Modulating Amyloid Oligomerization. Issue 1 (7th October 2016) - Zhao, Zijian; Zhu, Ling; Li, Haiyun; Cheng, Peng; Peng, Jiaxi; Yin, Yudan; Yang, Yang; Wang, Chen; Hu, Zhiyuan; Yang, Yanlian
Abstract : The oligomerization and aggregation of amyloid β (Aβ) play central role in the pathogenesis of Alzheimer's disease (AD). Molecular binding agents for modulating the formation of Aβ oligomers and fibrils have promising application potential in AD therapies. By screening a peptoid library using surface plasmon resonance imaging, amyloid inhibitory peptoid 1 (AIP1) that has high affinity to Aβ42 is identified. AIP1 is demonstrated to inhibit Aβ42 oligomerization and fibrillation and to rescue Aβ42‐induced cytotoxicity through decreasing the content of Aβ42 oligomers that is related to cell membrane permeability. Molecular docking suggests that the binding sites of AIP1 may be at the N‐terminus of Aβ42. The blood‐brain barrier (BBB) permeability of AIP1 using an in vitro BBB model is also revealed. This work provides a strategy for the design and development of peptoid‐based antiamyloidogenic agents. The obtained amyloid inhibitory peptoid shows prospects in the therapeutic application in AD. Abstract : Amyloid inhibitory peptoid 1 (AIP1) that has a high affinity to Aβ42 is identified as a Aβ42‐binding agent by screening a peptoid library. AIP1 is demonstrated to inhibit Aβ42 oligomerization and fibrillation, and to rescue Aβ42‐induced cytotoxicity through decreasing the content of Aβ42 oligomers that is related to cell membrane permeability. AIP1 exhibits great blood‐brain barrier permeability and holds promising potential for the therapeutic applications in Alzheimer's disease.